2003
DOI: 10.2535/ofaj.80.23
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variation of the Arm Artery: Coexistence with the Superficial Brachial and Superficial Subscapular Arteries in the Absence of the Normal Brachial Artery

Abstract: Summary: A rare variation in the arterial pattern was found in the right arm of an 87-year-old male cadaver in a student dissection practice. In this case, the superficial brachial and superficial subscapular arteries coexisted in the absence of the normal brachial artery (A. brachialis profunda). After branching off a large-sized superficial subscapular artery, the axillary artery did not penetrate the brachial plexus and gave rise to a superficial brachial artery, which arose from the axillary artery at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Another dissection found the axillary artery giving rise to super cial brachial and super cial subscapular arteries in the absence of a normal brachial artery. The super cial brachial artery then descended anterior to the brachial plexus and branched off a profunda brachii artery, while the super cial subscapular artery passed posterior to the plexus [9]. In another variation, the axillary artery passed normally between the lateral and medial cords, then bifurcated into large super cial brachial and deep brachial arteries [10].…”
Section: Discussionmentioning
confidence: 99%
“…Another dissection found the axillary artery giving rise to super cial brachial and super cial subscapular arteries in the absence of a normal brachial artery. The super cial brachial artery then descended anterior to the brachial plexus and branched off a profunda brachii artery, while the super cial subscapular artery passed posterior to the plexus [9]. In another variation, the axillary artery passed normally between the lateral and medial cords, then bifurcated into large super cial brachial and deep brachial arteries [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported variations in vessels of the upper limb presenting some interesting cases [1][2][3][4][5] . The theory regarding the vascular system development of the upper limb states that it begins at stage 12.…”
Section: Introductionmentioning
confidence: 99%